Environmental Management Physical Conditions and Complaints in The Health Workers in The Garment Production Gresik - Sajidah Baswedan; Lilis Sulistyorini (Universitas Airlangga, 2015)
Abstract: Physical conditions in the work environment is something that must be kept clean, because if the environmental conditions are not good, then it will result in the workers' health. This study aims to determine whether the management of the physical environmental conditions in the garment production in Gresik are in accordance with the Decree of the Minister of Health of the Republic of Indonesia Year 2002 Number 1405 About the Job Requirements Environmental Health Office and Industrial. This research uses descriptive and observational study using evaluative method. The results of the study will be treated descriptively. This study used a cross sectional approach. Sample size is 50 people who are working in garment production space in Gresik are taken randomly using simple random sampling. Obtained result is said to be good for the environment and are eligible for health complaints while ineligible said. Sheet observation shows that there are still some things about the application of the physical environmental conditions that are less in accordance with the regulations, among others, waste, noise, and toilet. Management of the physical environmental conditions in garment production space in Gresik can be categorized in accordance with applicable regulations.Keywords: physical conditions, health complaints